2014
DOI: 10.1016/j.cmet.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic β Cell Dedifferentiation in Diabetes and Redifferentiation following Insulin Therapy

Abstract: Diabetes is characterized by ‘glucotoxic’ loss of pancreatic β-cell function and insulin content, but underlying mechanisms remain unclear. A mouse model of insulin-secretory deficiency induced by β-cell inexcitability (KATP gain-of-function) demonstrates development of diabetes and reiterates the features of human neonatal diabetes. In the diabetic state, β-cells lose their mature identity and dedifferentiate to neurogenin3-positive and insulin-negative cells. Lineage-tracing experiments show that dedifferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
360
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(392 citation statements)
references
References 57 publications
26
360
3
3
Order By: Relevance
“…Dedifferentiation of beta cells is a topic of current islet research, and important contributions have been published by several groups in recent years during the course of this study [8,13,14]. In addition, Hang et al showed that MafA is required in adult beta cells for the maintenance of their phenotype but not for their initial differentiation [31], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Dedifferentiation of beta cells is a topic of current islet research, and important contributions have been published by several groups in recent years during the course of this study [8,13,14]. In addition, Hang et al showed that MafA is required in adult beta cells for the maintenance of their phenotype but not for their initial differentiation [31], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 81%
“…Reversing the dedifferentiation of insulin-negative beta cells restores beta cell function after the normalisation of hyperglycaemia [13,33], suggesting that beta cells are plastic until a certain stage. Our study suggests that inducing the redifferentiation of beta cells using extrinsic factors may be an effective treatment for diabetes and MafA may be a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, findings in transgenic mice suggest that new b-cells arise from existing b-cells (Dor et al 2004). Recent studies indicate that b-cells may dedifferentiate under metabolic stresses (Talchai et al 2012), and that insulin therapy can cause redifferentiation of dedifferentiated b-cells (Wang et al 2014). RYGB surgery resulting in b-cell redifferentiation may also lead to increased b-cell ratio and mass, as observed in our animal model.…”
Section: Discussionsupporting
confidence: 48%
“…their ability to transdifferentiate to other cell types (JONAS et al 1999;PAPIZAN et al 2011;TALCHAI et al 2012;WANG et al 2014). …”
Section: Discussionmentioning
confidence: 99%